Association between rural-to-urban migration and the onset of hypertension among middle-aged and older population: evidence from India - Bittu Mandal; Kalandi Charan Pradhan (BMC Public Health)
Abstract Background Rural-to-urban migration is a key contributor to urbanization in India and has potential implications for hypertension risk. Amidst the rising elderly population, the inequal burden of hypertension between migrants and non-migrants remains largely underexplored. This study examines the association between rural-to-urban migration and hypertension onset, focusing on rural-born individuals who have migrated to urban areas compared to those who have remained lifelong residents of rural areas. Methods Data from 27,270 participants aged 45 and above from the Longitudinal Ageing Study in India were analysed, including 18,855 non-migrant rural residents and 8,415 rural-to-urban migrants. The onset of hypertension was evaluated using bivariate statistics and the Cox proportional hazards model. Results Approximately 20% of rural non-migrants and 38% of rural-to-urban migrants were hypertensive. The median age of hypertension onset was 57 years for non-migrants and 54 years for migrants. Overall, migrants had a 1.22-fold (95% CI: 1.11–1.34) higher risk of hypertension onset. Regionally, migrants in the Northern (HR: 1.30, 95% CI: 1.10–1.53), Eastern (HR: 1.19, 95% CI: 0.99–1.44), and Southern regions (HR: 1.23, 95% CI: 1.07–1.43) were at a significantly higher risk of hypertension onset than their non-migrant peers. Conclusion These findings suggest that rural-to-urban migration may contribute to the early onset of hypertension in India, with notable variations across regions.